2017
DOI: 10.3892/etm.2017.5405
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin promotes the proliferation and differentiation of MC3T3-E1 cells via microRNA‑106b by targeting receptor activator of nuclear factor‑κB ligand

Abstract: Puerarin, an isoflavone-C-glucoside extracted from the root of Pueraria Labata (Willd.) Ohwi, is one of the most important crude herbs used in Chinese medicine for various medicinal purposes. Accumulating evidence has indicated that puerarin suppresses bone resorption and promotes bone formation. However, the molecular mechanism involved in puerarin-associated bone formation is unclear. The present study aimed to investigate the molecular mechanism of puerarin-induced osteoblast proliferation and differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Puerarin, an isoflavone extracted from the Chinese medicine pueraria, exhibits protective functions on the cardiovascular system, nervous system, osteoporosis, liver injury, and inflammation in vivo and in vitro (4). Studies have shown that puerarin can promote the proliferation, differentiation and mineralization of osteoblasts in vitro (5,6). In a recent report, puerarin was found to improve bone loss in estrogen-deficient rats, display a superior anti-osteoporosis effect, and prevent osteoporosis in postmenopausal women (7).…”
Section: Introductionmentioning
confidence: 99%
“…Puerarin, an isoflavone extracted from the Chinese medicine pueraria, exhibits protective functions on the cardiovascular system, nervous system, osteoporosis, liver injury, and inflammation in vivo and in vitro (4). Studies have shown that puerarin can promote the proliferation, differentiation and mineralization of osteoblasts in vitro (5,6). In a recent report, puerarin was found to improve bone loss in estrogen-deficient rats, display a superior anti-osteoporosis effect, and prevent osteoporosis in postmenopausal women (7).…”
Section: Introductionmentioning
confidence: 99%
“…It also alleviated osteopenia and prevented the deterioration of trabecular structure in mCT [ 99 ]. Other authors reported that puerarin inhibited RANKL-dependent osteoclastogenesis [ 100 ], induced mineral nodulus formation in osteoblasts through the activation of PI3K/AKT signalling pathway [ 101 ] and promotes osteoblast differentiation [ 102 ].…”
Section: Phytoestrogensmentioning
confidence: 99%
“…To date, a variety of treatment therapies have emerged, for instance, surgical intervention, mechanical forces, pharmacotherapy, cell therapy and molecular biology therapy [2][3][4][5], as well as a combination of several methods. Bioactive agents in combination with targeted therapeutics have drawn researchers' attention, especially through modulating microRNAs (miRs) and signalling pathways for accelerating osteoblastogenesis [6,7]. Given that preosteoblasts are bone-forming cells, it provides us a new insight into accelerating fracture healing by stimulating cells differentiation for bone formation.…”
Section: Introductionmentioning
confidence: 99%